A call to caution when hydroxychloroquine is given to elderly patients with COVID-19. (May 2021) - Gabor, Julian J.; Kreidenweiss, Andrea; Weber, Stefan; Salama, Moaaz; Sulyok, Mihaly; Sulyok, Zita; Koehne, Erik; Esen, Meral; Kreuels, Benno; Shamsrizi, Parichehr; Biecker, Erwin; Mordmüller, Benjamin; et al.
Highlights: Uncontrolled use of hydroxychloroquine in patients with coronavirus disease 2019 (COVID-19) was widespread until recently. Patients vulnerable to severe COVID-19 are at risk for hydroxychloroquine drug interactions. Co-morbidities and co-medications bear risks in treatment with hydroxychloroquine. Stringent screening is mandatory for hydroxychloroquine trials for safe enrolment of patients with COVID-19. Hydroxychloroquine should be administered with extreme caution in elderly patients. Abstract: Introduction: Use of hydroxychloroquine in patients with coronavirus disease 2019 (COVID-19) was widespread and uncontrolled until recently. Patients vulnerable to severe COVID-19 are at risk of hydroxychloroquine interactions with co-morbidities and co-medications contributing to detrimental, including fatal, adverse treatment effects. Methods: A retrospective survey was undertaken of health conditions and co-medications of patients with COVID-19 who were pre-screened for enrolment in a randomized, double-blind, placebo-controlled hydroxychloroquine multi-centre trial. Results: The survey involved 305 patients [median age 71 (interquartile range 59–81) years]. The majority of patients ( n = 279, 92%) considered for inclusion in the clinical trial were not eligible, mainly due to safety concerns caused by health conditions or co-medications. The most common were QT-prolonging drugs ( n = 188, 62%) and haematologic/haemato-oncologic diseases ( n = 39, 13%) which prohibited the administration of hydroxychloroquine. In addition, 165 (54%) patients had health conditions and 167 (55%) patients were on co-medications that did not prohibit the use of hydroxychloroquine but had a risk of adverse interactions with hydroxychloroquine. The most common were diabetes ( n = 86, 28%), renal insufficiency ( n = 69, 23%) and heart failure ( n = 58, 19%). Conclusion: The majority of hospitalized patients with COVID-19 had health conditions or took co-medications precluding safe treatment with hydroxychloroquine. Therefore, hydroxychloroquine should be administered with extreme caution in elderly patients with COVID-19, and only in clinical trials.